Survival rate and growth of juvenile vannamei shrimp (Litopenaeus vannamei) in different media water salinity - Abdul Rakhfid; Erna; Rochmady; Fendi; Muhammad Zayani Ihu; Karyawati (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2019)
Shrimp commodities in Indonesia have been cultivated, either traditionally, traditionally plus, semi intensive, or intensively. One type of shrimp that is constantly strived to increase its production is the shrimp vaname (Litopenaneus vannamei). The environmental conditions of pond waters are closely related to pond water quality. One of the water quality parameters affecting the survival and growth of vaname shrimp is salinity. The study was conducted from May to June 2018 at the Fish Seed Hall (BBIP) Ghonebalano, Ghonebalano Village, Duruka District, Muna Regency. This study aims to determine the effect of water salinity on different media on the survival and growth of vaname shrimp. The study used a Completely Randomized Design with four treatments and three replications. Treatment A salinity 20 ppt, B treatment salinity 25 ppt, C treatment salinity 30 ppt and treatment D salinity 35 ppt. The results showed that the treatment had significant effect on the survival of the animals in the 95% confidence level where the survival in sequence, the treatment of A 87.50%, the treatment of B 83.33%, the C treatment 80.56% and the treatment D 69.44% . The treatment also had a significant effect on the growth of test animal at 95% confidence level. Successive growth was, treatment A 2.01 g, treatment B 1.91 g, treatment C 1,71 g and treatment D 1.51 g.